The selective neurotoxin DSP-4 impairs the noradrenergic projections from the locus coeruleus to the inferior colliculus in rats - Hormigo, Sebastián; e Horta Junior, José de Anchieta d.; Gómez-Nieto, Ricardo; López García, Dolores E. (Frontiers in Neural Circuits, 2012)
The inferior colliculus (IC) and the locus coeruleus (LC) are two midbrain nuclei that integrate multimodal information and play a major role in novelty detection to elicit an orienting response. Despite the reciprocal connections between these two structures, the projection pattern and target areas of the LC within the subdivisions of the rat IC are still unknown. Here, we used tract-tracing approaches combined with immunohistochemistry, densitometry and confocal microscopy analysis to describe a projection from the LC to the IC. Biotinylated dextran amine (BDA) injections into the LC showed that the LC-IC projection is mainly ipsilateral (90%) and reaches, to a major extent, the dorsal and lateral part of the IC and the intercollicular commissure. Additionally, some LC fibers extend into the central nucleus of the IC. The neurochemical nature of this projection is noradrenergic, given that tyrosine hydroxylase (TH) and dopamine beta hydroxylase (DBH) colocalize with the BDA-labeled fibers from the LC. To determine the total field of the LC innervations in the IC, we destroyed the LC neurons and fibers using a highly selective neurotoxin, DSP-4, and then studied the distribution and density of TH- and DBH-immunolabeled axons in the IC. In the DSP-4 treated animals, the number of axonal fibers immunolabeled for TH and DBH were deeply decreased throughout the entire rostrocaudal extent of the IC and its subdivisions compared to controls. Our densitometry results showed that the IC receives up to 97% of its noradrenergic innervations from the LC neurons and only 3% from non-coeruleus neurons. Our results also indicate that TH immunoreactivity in the IC was less impaired than the immunoreactivity for DBH after DSP-4 administration. This is consistent with the existence of an important dopaminergic projection from the substantia nigra to the IC. In conclusion, our study demonstrates and quantifies the noradrenergic projection from the LC to the IC and its subdivisions.